A quantitative method study on pertechnetate in aqueous solution using Raman spectroscopy. Issue 7 (28th January 2016) - Zhang, Qianci; Zhu, Haiqiao; Chang, Zhiyuan; Luo, Zhongyan; Bai, Xue; Li, Dingming
Abstract : The quantification of TcO4 − in aqueous solutions simply using Raman spectroscopy with NO3 − and water as internal standards without a sample preparation step. Abstract : Technetium is an important fission product in the reprocessing process of spent fuels, and its determination is of great significance in nuclear chemistry and technology. However, nearly all related methods need a pretreatment step before measurement, the study proposed herein focused on the quantification of TcO4 − in aqueous solutions simply using Raman spectroscopy with NO3 − and water as internal standards without a sample preparation step. The relative intensity of TcO4 − to NO3 − (1047 cm −1 ) and OH (1645 cm −1 ) showed good linearity to the concentration of TcO4 − . The molar relative intensity was calculated for determination, and the predictions of these samples using both estimating methods were acceptable. The work also studied the behavior of TcO4 − in a complex matrix, the results show that it is possible to use Raman spectroscopy for TcO4 − quantitative determination in aqueous solution. The LOD and LOQ obtained is 0.42 mmol L −1 and 1.39 mmol L −1, respectively.